Preparation of mesoporous activated carbon from Kraft lignin by impregnation with H2SO4: A four parameters optimization study. Issue 4 (31st October 2012) - Li, Xianfa; Luo, Xuegang
<x xml:space="preserve">Abstract</x> Activated carbons (ACs) were prepared from waste Kraft lignin (KL) obtained from pulp and paper industry by chemical activation with H2SO4. The KL was characterized by elemental analysis and thermal gravimetric analysis. The suitable process conditions were optimized by an orthogonal design test [L9 (34)], factors including the activation temperature, concentration of H2SO4, activation time, and N2 flow rate. The morphology and pore structure of ACs were investigated by means of scanning electron microscopy, cryogenic N2 adsorption isotherm. The orthogonal test results suggested that the optimal activation parameters were as follows: 600°C of activation temperature, 35% of H2SO4 concentration, 120 min of activation time, and 100 cm3/min of N2 flow rate. Under the selected conditions, a mesoporous ACs with BET surface area of 873.9 m2/g and total pore volume of 0.485 cm3/g was obtained. The ACs obtained from KL by H2SO4 activation were also compared with ACs prepared by H3PO4 and KOH activation. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 1158–1163, 2013